2008
DOI: 10.1073/pnas.0804445105
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome mutational biases in bacteria

Abstract: A fundamental biological question is what forces shape the guanine plus cytosine (GC) content of genomes. We studied the specificity and rate of different mutational biases in real time in the bacterium Salmonella typhimurium under conditions of strongly reduced selection and in the absence of the major DNA repair systems involved in repairing common spontaneous mutations caused by oxidized and deaminated DNA bases. The mutational spectrum was determined by whole-genome sequencing of two S. typhimurium mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
158
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 35 publications
(34 reference statements)
19
158
3
Order By: Relevance
“…None of these values is significantly different from expected (P ≥ 0.42 in every case). Thus, our results do not support previous observations that highly expressed genes have either high (11,35,36) or low (37-39) mutation rates. Unlike a previous report (39), we found no bias for any type of base change occurring preferentially on either the transcribed or the nontranscribed DNA strand (Table S3).…”
Section: Distribution Of Mutations Is Random Among Wild-type Lines Bucontrasting
confidence: 99%
See 1 more Smart Citation
“…None of these values is significantly different from expected (P ≥ 0.42 in every case). Thus, our results do not support previous observations that highly expressed genes have either high (11,35,36) or low (37-39) mutation rates. Unlike a previous report (39), we found no bias for any type of base change occurring preferentially on either the transcribed or the nontranscribed DNA strand (Table S3).…”
Section: Distribution Of Mutations Is Random Among Wild-type Lines Bucontrasting
confidence: 99%
“…The application of whole-genome sequencing to MA lines has made this protocol an extremely valuable way to determine a complete and nearly unbiased picture of mutation profiles. Recent results from applying this protocol to microbes include the genomewide spontaneous mutational spectrum in Saccharomyces cerevisiae (10) and the mutational consequences of loss of DNA oxidative damage repair in Salmonella typhimurium (11).…”
mentioning
confidence: 99%
“…Universal transition and G:C . A:T biases have also been observed in all MA studies to date (Lind and Andersson 2008;Lynch et al 2008;Denver et al 2009;Ossowski et al 2010;Lee et al 2012;Sung et al 2012a,b), corroborating previous findings using indirect methods (Hershberg and Petrov 2010;Hildebrand et al 2010). However, several additional characteristics of mutation spectra vary among species (Lynch et al 2008;Denver et al 2009;Ossowski et al 2010;Lee et al 2012;Sung et al 2012a,b), and examining the role of genome architecture, size, and lifestyle in producing these idiosyncrasies will require a considerably larger number of detailed MA studies.…”
supporting
confidence: 72%
“…The lack of mutational bias toward AT bases observed in B. cenocepacia has not been seen previously in nonmutator MA lineages of any kind (Lind and Andersson 2008;Lynch et al 2008;Denver et al 2009;Keightley et al 2009;Ossowski et al 2010;Lee et al 2012;Sung et al 2012a,b). However, selection and/or biased gene conversion must still be invoked to explain the high %GC content in B. cenocepacia (Hershberg and Petrov 2010;Hildebrand et al 2010).…”
Section: Discussionmentioning
confidence: 47%
“…However, recent studies have shown that the variation of the GC content among bacteria is driven by selection, in which mutations from GC to adenosine-thymine (AT) are more common than mutations from AT to GC (Hershberg and Petrov, 2010;Hildebrand et al, 2010;Rocha and Feil, 2010). Lind and Andersson (2008) compared the genomes of 2 Salmonella typhimurium mutants and showed a bias toward mutations from GC to AT. Rocha and Danchin (2002) suggested that GC content variation may be related to the higher energy cost and limited availability of G and C over A and T. However, many bacterial species such as Actinobacteria have a high GC content genome.…”
Section: Distribution Of Genome Base Compositions and Mutational Biasesmentioning
confidence: 99%